Identifying and Ranking new product development critical factors based on marketing strategy case study Esfahan Steel Co. - Dashtianeh, Ehsan; Radfar, Reza; Toloui Oshlohi, Abbas (Brazilian Journal of Operations & Production Management, 2021)
Goal: Increasing orders and selling products are essential factors in designing all industries’ strategy. To improving this factor, researchers have suggested many ways, such as new product development. By succeeding in designing and introducing a new product, each company would gain a better market share. One of the best examples of this d innovation competition in companies is in the IT market where all companies compete for innovation and product development. Globally most of the roles are in common; however, some change according to the market, social, and political environment. For a successful new product in any industry, the marketing team should know their goal society’s market environment and prioritize and choose the best marketing strategy according to their data analysis. Design / Methodology / Approach: In this paper, initially, critical factors in successful new product development (NPD) at Esfahan Steel Co. are identified using a systematic literature review. Later, by using the information provided from the HR and marketing department of the Esfahan Steed Co., the designed questionnaire is asked to be filled by expertise, suppliers and customers. The collected data is analyzed by Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), and the main parameters affecting successful NPD is identified. Results: In this study, fifteen factors are extracted from the literature and ranked by TOPSIS method. All of the fifteen factors are divided into five main categories: customer behavior, supplier, market, government strategy and social media. The results showed that the customer’s needs and government role is the most crucial factor in alloy market. Limitations of the investigation: In this study, the international sanctions imposed by the UN and the USA was intrusive variables that affected the study results, because this variable affected the study data and responder answer. Practical implications: Market strategy is one of the essential factors of success in all companies. This study showed that the marketing strategy of Esfahan Steel Co. could be improved. Originality / Value: This study highlighted the differences in Iran’s steel market from other markets which are presented in the literature.